(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The effects of vehicle-structure interaction have a significant importance on the dynamic responses of both systems with several applications within the highways field. If the vehicle-irregularities-bridge dynamic interaction is capable to produce accumulated strains that cause damage to the structure, the dynamic responses are affected. By crossing a highway bridge with any speed, the vehicle is subjected to the highway irregularities. The movement of a vehicle on a bridge is already a dynamic action on the structure. However, the highway irregularities tend to excite the vehicle dynamically which in turns triggers additional vibrations in the highway bridge structure apart from those produced by their own movement, increasing the bridge’s damage evolution. This modifies the dynamic responses of the structure, increasing the magnitude and the oscillations particularly at critical speeds of the vehicle, capable to provoke some resonance. Apart from changing the displacements, velocities and accelerations responses, the damage alters the structural natural frequencies of vibration. Such effects are not possible to be analysed with linear dynamic models. The nonlinearities occur by the fact that the forces no longer linearly depend from the displacements when damage occurs. This work aims to evaluate the nonlinear dynamic damage evolution of a reinforced concrete highway bridge through the Finite Element Method, on which the degree of damage is altered over time by the dynamic interaction with random irregularities and moving vehicles due to the stiffness loss of the structure by Damage Mechanics. The highway irregularities are represented by random functions. Euler-Bernoulli beam elements with Hermite cubic interpolation functions are used for the bridge model. The Mazars Damage Constitutive Model is implemented with the condition of stress inversion due to vibration. The continuum damage mechanics is considered dynamically. Therefore, the damage is evaluated in each layer of the structure cross section for each iteration within each time step. The structural damping is defined by the Rayleigh method with updated coefficients due to damage. The equations of motion are obtained by nonlinear dynamic equilibrium and numerically integrated in time using the Newmark Method together with the Newton-Raphson iterative Method. This proposal seeks to contribute to the study of the health monitoring and the structural integrity of damaged highway bridges structures.